1998
DOI: 10.1002/(sici)1098-2264(199806)22:2<157::aid-gcc11>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Virtually 100% of melanoma cell lines harbor alterations at the DNA level withinCDKN2A, CDKN2B, or one of their downstream targets

Abstract: The cyclin‐dependent kinase inhibitor 2A (CDKN2A), or p16INK4a, gene on 9p21 is important in the genesis of both familial and sporadic melanoma. Homozygous deletions and intragenic mutations of this gene have been identified in both melanoma cell lines and uncultured tumors, although the frequency of these alterations is higher in the cell lines. A proportion of melanoma cell lines and tumors without deletion/mutation of CDKN2A have also been determined to harbor transcriptionally inactive CDKN2A alleles or ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(89 citation statements)
references
References 25 publications
(23 reference statements)
2
84
0
3
Order By: Relevance
“…The RB family proteins are transcriptional regulators, of which the best-characterized function in the inhibition of proliferation is to suppress transactivation by the E2F family of transcription factors (Figure 1). The RB pathway appears critically important in the suppression of melanoma development, since all or nearly all human melanoma lines tested show disruption of this pathway, via p16 or RB1 deficiency, CDK4 mutation or overexpression of cyclin D1 (Bartkova et al, 1996;Walker et al, 1998). ARF acts in a different pathway, namely by indirectly activating yet another key tumor-and growthsuppressor, p53.…”
Section: Melanoma Susceptibility Genes and Their Cellular Functionsmentioning
confidence: 99%
“…The RB family proteins are transcriptional regulators, of which the best-characterized function in the inhibition of proliferation is to suppress transactivation by the E2F family of transcription factors (Figure 1). The RB pathway appears critically important in the suppression of melanoma development, since all or nearly all human melanoma lines tested show disruption of this pathway, via p16 or RB1 deficiency, CDK4 mutation or overexpression of cyclin D1 (Bartkova et al, 1996;Walker et al, 1998). ARF acts in a different pathway, namely by indirectly activating yet another key tumor-and growthsuppressor, p53.…”
Section: Melanoma Susceptibility Genes and Their Cellular Functionsmentioning
confidence: 99%
“…The CDKN2A locus accounts for susceptibility in $25% of all melanoma families (Bishop et al, 2002), whereas mutations in the CDK4 oncogene are rare (Zuo et al, 1996;Soufir et al, 1998;Molven et al, 2005). In addition to germline changes, somatic mutations of both CDKN2A and CDK4 occur during melanoma development (Castellano et al, 1997;Whiteman et al, 1997;Monzon et al, 1998;Walker et al, 1998;Auroy et al, 2001). Apart from CDK4, other oncogenes thus far identified to play a significant role in melanoma tumorigenesis encode components of the mitogen-activated protein kinase (MAPK) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly altered targets identi®ed thus far include chromosome arms 1q, 6q, 9p, 10q and 11q (Albino, 1995;Welch and Goldberg, 1997). Recently, alterations of the tumour suppressor genes p16 INK4/CDKN2 and PTEN/MMAC1 on 9p and 10q, respectively, have been demonstrated in signi®cant proportions of melanoma lesions and cell lines (Kamb et al, 1994;Bartkova et al, 1996;Castellano et al, 1997;Guldberg et al, 1997;Walker et al, 1998;Tsao et al, 1998), and the AIM1 gene has been suggested as a good candidate for the putative tumour suppressor on chromosome 6 (Ray et al, 1997).…”
mentioning
confidence: 99%
“…Alternatively, they may represent molecular tumour-suppressive pathways that are abrogated only rarely in melanoma, or they may represent rarely altered components of commonly altered pathways. An example of the latter situation is the p16-cyclin D/ Cdk4-pRB pathway which is abrogated through alteration of one of its components in virtually all melanoma cell lines, yet with p16 INK4/CDKN2 being by far the most common genetic target (Bartkova et al, 1996;Walker et al, 1998).…”
mentioning
confidence: 99%